Hydrogeochemical assessment of groundwater and surface water in Pomalaa District, Kolaka Regency, Southeast Sulawesi - Rahmawati Erisa; Masitoh Ferryati; Mararis Denis; Kurniawan (BIO Web of Conferences)
Pomalaa is one of the area mining activities that significantly impact water quality due to increased concentrations of major elements. The research objective to analyze hydrogeochemical processes in groundwater and surface water in Pomalaa. The hydrogeochemical process is important to identify and control the process of groundwater and surface water interaction with minerals. The method used is geological and hydrogeochemical analysis based on the major elements. Sampling used random sampling. The primary data included 20 laboratory test samples and 3 drill log data. The secondary data included regional geological data. The Processing was conducted using RockWorks software and presented through the Kurlov Classification, Durov Diagram, Trilinear Piper Diagram, and Schoeller Diagram. The results of the Kurlov Classification and The Schoeller have shared a high cation content in Calcium and Magnesium and a high anion in Chloride and Sulfate. The high cation indicates geological formations contain Calcium and Magnesium. The high anion indicates rocks originating from the oceanic crust, formed due to high pressure and temperature, then exposed to the earth's surface due to tectonism. The Piper Diagram results show that the water is classified as alkaline earth water with higher alkaline content, predominantly Sulfate or Chloride. The Durov Diagram is classified as simple dissolution or mixing. The geological analysis results are consistent with the hydrogeochemical analysis, and the area shows the interaction between rocks and water in the study area. This research is important to provide information on geological water quality and hydrogeochemical analysis in Pomalaa.